Effect of microalloying elements on austenite grain growth in Nb–Ti and Nb–V steels. (June 2014) - Karmakar, A.; Kundu, S.; Roy, S.; Neogy, S.; Srivastava, D.; Chakrabarti, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Development of austenite grain structures have been compared in two different microalloyed steels (Nb–Ti and Nb–V steels) and one Al killed C–Mn steel, after soaking at 950–1250°C for 1 h. Minimum austenite grain size in Nb–V steel at the lower soaking temperature (<1075°C) can be attributed to the pinning effect from AlN, Nb(C, N) and V(C, N) precipitates. At the intermediate soaking temperatures (1150–1200°C) dissolution of Nb precipitates led to an abnormal austenite grain growth and the formation of bimodal grain size distributions in microalloyed steels. Grain size bimodality was more severe in Nb–V steel as compared to Nb–Ti steel. Complete absence of precipitates allowed the austenite grains to grow freely at higher soaking temperature (>1200°C) in all the steels. Higher stability of TiN precipitate restricted the grain growth in Nb–Ti steel at higher soaking temperature. An effort has been made to predict the austenite grain size considering both solute drag and Zener drag.